Design, synthesis, and biological evaluation of novel tetrahydroprotoberberine derivatives (THPBs) as proprotein convertase subtilisin/kexin type 9 (PCSK9) modulators for the treatment of hyperlipidemia - Chenglin Wu; Cong Xi; Junhua Tong; Jing Zhao; Hualiang Jiang; Jiang Wang; Yiping Wang; Hong Liu (Acta Pharmaceutica Sinica B, 2019)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) modulators may attenuate PCSK9-induced low-density lipoprotein receptor (LDLR) degradation in lysosome and promote the clearance of circulating low-density lipoprotein cholesterol (LDL-C). A novel series of tetrahydroprotoberberine derivatives (THPBs) were designed, synthesized, and evaluated as PCSK9 modulators for the treatment of hyperlipidemia. Among them, eight compounds exhibited excellent activities in downregulating hepatic PCSK9 expression better than berberine in HepG2 cells. In addition, five compounds 15, 18, 22, (R)-22, and (S)-22 showed better performance in the low-density lipoprotein, labeled with 1,1′-dioctadecyl-3,3,3′,3′-tetramethyl-indocarbocyanine perchlorate (DiI-LDL) uptake assay, compared with berberine at the same concentration. Compound 22, selected for in vivo evaluation, demonstrated significant reductions of total cholesterol (TC) and LDL-C in hyperlipidemic hamsters with a good pharmacokinetic profile. Further exploring of the lipid-lowering mechanism showed that compound 22 promoted hepatic LDLR expression in a dose-dependent manner in HepG2 cells. Additional results of human ether-à-go-go related gene (hERG) inhibition assay indicated the potential druggability for compound 22, which is a promising lead compound for the development of PCSK9 modulator for the treatment of hyperlipidemia. Key words: PCSK9, Tetrahydroprotoberberine derivatives, Low-density lipoprotein cholesterol, Lipid-lowering, PCSK9 expression, Low-density lipoprotein receptor, Total cholesterol, Hyperlipidemia hamster